Virtual Alentejo: Analysis and reflection on a 360º virtual tour - Noronha Sousa, Marta (Aprender, 2024)
Tourism is increasingly making use of digital technologies, including Virtual Reality, to promote its offer, seeking to adapt to current society trends. Following this logic, Turismo do Alentejo created an online portal, Visit Alentejo, which provides a 360º virtual visit to multiple tourist sites in the region. The goal of this work is to understand to what extent this virtual visit capitalizes on the potential of technology and audiovisual language to achieve maximum communicative and effective potential in promoting Alentejo as a tourist destination. In this sense, a corpus of specific visits was selected and qualitatively analyzed, at the level of content (type of information offered), form (media formats used and their formal and stylistic features) and the interaction the visit allows the user. We then discuss the results in light of the theoretical framework presented, in the convergence of tourism, virtual reality and media studies, and reflect upon the potential virtues and limitations of the virtual visit, offering suggestions to make it more appealing. The main suggestion concerns the creation of additional narrative content, in audio and video format, that allows “populating” the virtual environment and illustrating the identity and authenticity of the Alentejo people and territory.
Keywords: 360º virtual tour; audiovisual language; narrative; tourism; virtual reality